KEGAGALAN PRIVATISASI BUMN DI ERA REZIM ORDE BARU DALAM PERSPEKTIF EKONOMI POLITIK - Syamsul Ma'arif (P3M STISIPOL Dharma Wacana Metro, 2018)
After had being carried out nationalization and hostility against west countries, the New Order regime made important decision to change Indonesia economic direction from etatism system to free market economy. A set of policies were taken in order private sector could play major role in economic. However, when another economic sectors were reformed substantially, effords to reform the State Owned Enterprises had failed. The State Owned Enterprise, in fact, remained to play dominant role like early years of guided democracy era. Role of the State Owned Enterprises was more and more powerfull). The main problem of reforms finally lied on reality that vested interest of bureaucrats (civil or military) was so large that could’nt been overcome.